2010
DOI: 10.2527/jas.2009-2498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulfur and monensin concentrations on in vitro dry matter disappearance, hydrogen sulfide production, and volatile fatty acid concentrations in batch culture ruminal fermentations1

Abstract: Effects of monensin (MON) and S on in vitro fermentation and H(2)S production were evaluated in 2 experiments. In Exp. 1, 2 ruminally cannulated steers were adapted (>14 d) to a 75% concentrate diet [steam-flaked corn (SFC)-based], and ruminal fluid was collected approximately 4 h after feeding. Substrate composed (DM basis) of 85.2% SFC, 9% alfalfa hay, 5% cottonseed meal, and 0.8% urea was added with ruminal fluid and buffer to sealed 125-mL serum bottles to allow for gas collection. A Na(2)SO(4) solution wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 25 publications
5
26
3
Order By: Relevance
“…The IVD of the nutrients was determined in triplicate, using the one-stage technique described by Silva and Queiroz (2002) and adapted to a 24-h fermentation stage as described by Smith et al (2010). Sheep ruminal fluid was collected by vacuum suction pump in the morning, 2 h after the morning feed in order to obtain a suitable microbial population and a minimum number of food particles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IVD of the nutrients was determined in triplicate, using the one-stage technique described by Silva and Queiroz (2002) and adapted to a 24-h fermentation stage as described by Smith et al (2010). Sheep ruminal fluid was collected by vacuum suction pump in the morning, 2 h after the morning feed in order to obtain a suitable microbial population and a minimum number of food particles.…”
Section: Methodsmentioning
confidence: 99%
“…Every 2 h, the tubes were gently shaken manually to aid the release of formed gases. Three tubes containing only incubation solution were incubated in each run to serve as controls, and three tubes containing only Tifton 85 hay (Cynodon) as index forage (SMITH et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of monensin is a function of the dosage. Two in vitro experiments reported that monensin decreased gas production and that the doses were higher than those used in animal feeds (Smith, 2010;Kim et al, 2014a). In contrast, Singh and Mohani (1999) did not find any effect on in vitro gas production using 50 or 100 mg/d of monensin in rumen fluid donors.…”
Section: Discussionmentioning
confidence: 97%
“…In each battery, three tubes were placed in an experimental ration containing 0% or 15% RETP which was then incubated with two types of inoculum (sheep ruminal fluid and feces). The samples then underwent 24 h of in vitro fermentation, as adapted from the technique of Smith et al (2010). The IVD of nutrients assay was conducted after the test in vivo digestion.…”
Section: Methodsmentioning
confidence: 99%